Upregulation of Toll-like receptor 2 and nuclear factor-kappa B expression in experimental colonic schistosomiasis - Ashour, Dalia S.; Shohieb, Zeinab S.; Sarhan, Naglaa I. (Journal of advanced research, 2015)
Role of different mediators was described in the development of the granulomatous response and fibrosis observed in intestinal schistosomiasis. However, both Toll-like receptor 2 (TLR2) and nuclear factor kappa B (NF-κB) have not yet been investigated in intestinal schistosomiasis. This study aimed to characterize the role of TLR2 and NF-κB in the pathogenesis of intestinal schistosomiasis. Experimental animals were divided into two groups; group I: non-infected control group and group II: mice infected subcutaneously with S. mansoni cercariae. Colon samples were taken from infected mice, every two weeks, starting from the 6th week postinfection (PI) till 18th week PI. Samples were subjected to histopathological and immunohistochemical studies. Colon of S. mansoni infected mice showed histopathological changes in the form of mucosal degeneration, transmural mononuclear cellular infiltration and granulomas formation. Immunostained sections revealed significant increase in TLR2 and NF-κB positive cells in all layers of the colon, cells of the granuloma and those of the lymphoid follicles 10weeks PI. All these changes decreased gradually starting from 12weeks PI onward to be localized focally at 18weeks PI. In conclusion, recruitment and activation of inflammatory cells to the colonic mucosa in intestinal schistosomiasis are multifactorial events involving TLR2 that can trigger the NF-κB pathways. Hence, down-regulation of both TLR2 and NF-κB could be exploited in the treatment of colonic schistosomiasis.